2008
DOI: 10.1093/deafed/enn011
|View full text |Cite
|
Sign up to set email alerts
|

Literacy Skills in Children With Cochlear Implants: The Importance of Early Oral Language and Joint Storybook Reading

Abstract: The goal of this study was to longitudinally examine relationships between early factors (child and mother) that may influence children's phonological awareness and reading skills 3 years later in a group of young children with cochlear implants (N = 16). Mothers and children were videotaped during two storybook interactions, and children's oral language skills were assessed using the "Reynell Developmental Language Scales, third edition." Three years later, phonological awareness, reading skills, and language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
1
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 70 publications
6
65
1
8
Order By: Relevance
“…The strong association between receptive language and early reading is therefore not a surprising finding, although DesJardin et al (14) found expressive language to be more predictive. The additional impact of reading on language gaps is of particular importance in children with CIs as they struggle to catch up and keep up with their hearing peers.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The strong association between receptive language and early reading is therefore not a surprising finding, although DesJardin et al (14) found expressive language to be more predictive. The additional impact of reading on language gaps is of particular importance in children with CIs as they struggle to catch up and keep up with their hearing peers.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the extent of literacy development is related to how frequently children participate in analytical talk including the making of predictions and inferences (9). Parental use of complex and facilitative language in daily communication (12) and joint reading (13,14) has also been reported to influence the language development and reading performance of children with CIs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that degraded sensory inputs will negatively impact oral language development in children with hearing loss (Briscoe, Bishop, & Norbury, 2001;StoelGammon, 1988;Yoshinaga-Itano, Sedey, Coulter, & Mehl, 1998), whereas appropriate auditory stimulations will play a major role in both phonological and lexical development (Desjardin, Ambrose, & Eisenberg, 2009;Farran, Ledesberg, & Jackson, 2009). Recent studies using LENA also point in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…21 Ask families of newly identified infants/ children who are D/HH annually whether they received the family resource manual and if a service coordinator or EI provider reviewed the information with them. 28 Goal 3 (and Appendix 1) promotes reliance on qualified providers, and recommends processes for ensuring that families access them. Goals 3a and 3b are not intended to be mutually exclusive; rather, they describe key quality elements when providers are using spoken or visual languages.…”
Section: Share a Baseline Analysis Of Ehdimentioning
confidence: 99%